Pengaruh Celebrity Endorser (Sehun), Brand Trust, dan Viral Marketing Terhadap Keputusan Pembelian Produk Whitelab : Studi Pemasaran Produk Whitelab Pada Followers Instagram @Whitelab.Id - Jeciska Shelly F. Sihombing; Hafiza Adlina (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
At the present time, the utilisation of social media is expanding at an unprecedented rate. Many individuals are connected through social media, which has created extraordinary business opportunities. As a result, purchasing and selling activities have become more dynamic and have reached a broader audience. This research endeavours to evaluate the impact of viral marketing, brand trust, and celebrity endorsers (Sehun) on the purchasing decisions of Whitelab Instagram followers. The research employed is quantitative and employs an associative approach. Followers of whitelab Instagram were the population of this investigation. This investigation employed probability sampling with a sample of 100 respondents. Primary data was acquired by disseminating questionnaires online using Google Forms, while secondary data was acquired through literature studies. The research conducted has revealed that the variables of celebrity endorser (Sehun), brand trust, and viral marketing have a substantial impact on the purchasing decisions of Whitelab products among Whitelab Instagram followers, both partially and simultaneously. The coefficient of determination test indicates that there is a strong correlation between celebrity endorsers (Sehun), brand trust, and viral marketing in relation to purchasing decisions, with a R value of 0.860. According to the Adjusted R Square value or coefficient of determination, the celebrity endorser (Sehun) variable (X1), brand trust (X2), and viral marketing (X3) can account for 73.2% of the purchasing decision variable (Y). The remaining 26.8% is influenced by variables that are not addressed in this study.